Magician’s Corner: 7. Using Convolutional Neural Networks to Reduce Noise in Medical Images - Huber, Nathan Robert (Radiol Artif Intell, 2020)
This article shows how to train a convolutional neural network to reduce noise in CT images, although the principles apply to medical and nonmedical images; authors also explore mathematical and visually weighted loss functions to adjust the appearance.